Left ventricular rotational mechanics in elite athletes doing high dynamic sports. Insights from the 3D speckle-tracking echocardiographic MAGYAR-Sport Study - Gyenes, N.; Kormanyos, Á.; Vagvölgyi, A.; Domsik, P.; Kalapos, A.; Ambrus, N.; Lengyel, C.; Balogh, L.; Pucsok, J.; Nemes, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: In normal circumstances while left ventricular (LV) apex rotates counterclockwise, LV base has a clockwise movement at the same time. This sort of towel-wringing-like movement is called LV twist. The present study was designed to test whether differences in LV rotational mechanics could be detected in elite athletes doing high dynamic sports with different static components in their training. METHODS: The subject group comprised 80 elite sportsmen. The following groups were created regarding their physical activity: group CI (high dynamic/low static) (N.=13, mean age: 24.0±5.1 years, group CII (high dynamic/moderate static) (N.=23, mean age: 24.6±7.7 years) and group CIII (high dynamic/high static)(N.=34, mean age: 22.8±6.0 years). Their results were compared to 67 age- and gender-matched non-athletic healthy controls (mean age: 24.0±5.1 years). Three-dimensional speckle-tracking echocardiography was used for the evaluation of LV rotational abnormalities. RESULTS: Reduced LV basal rotation was seen in group CII and CIII subjects compared to the control group (-4.31±1.82 degrees vs. -3.17±2.81 degrees and -2.88±1.88 degrees, P<0.05 and P<0.05, respectively). It was accompanied with LV twist reduction in groups CII and CIII subjects compared to the control group (14.0±3.4 degree vs. 11.3±4.3 degrees and 11.5±4.1 degrees, P<0.05 and P<0.05, respectively). None of the elite athletes showed absence of LV twist called as LV "rigid body rotation." CONCLUSIONS: Significant LV rotational abnormalities including reduced LV basal rotation and twist could be detected in elite athletes doing high dynamic sports with moderate/high static components in their training.